Human Absorbed Dose Evaluation of [177Lu]Lu-IBA as a Bone Palliative Candidate - Ranjbar, Hassan; Pourhabib, Zahra (Nuklearmedizin - NuclearMedicine, 2021)
The role of lutetium-177 among bone-seeking radionuclides in targeted therapy is noteworthy. The clinical pharmacokinetics of ibandronate (IBA) indicates that this bisphonate has powerful bone mineral affinity. The aim of this study was to evaluate of [177Lu]Lu-IBA efficacy as a new compound.The [177Lu]Lu-IBA was prepared by radiolabeling of IBA ligand to 177LuCl3 that was obtained by thermal neutron irradiation of enriched Lu2O3 sample. Produced [177Lu]Lu-IBA with high radiochemical purity was administered intravenously to mice. Biodistribution data were collected at 1, 4, 24, 48 h and 7 d post injections. With calculating accumulated activities in each organ and extrapolating mouse’s organs to human’s organs by the RADAR method and using OLINDA/EXM software the injected dose in various human organs was achieved.[177Lu]Lu-IBA was produced with radiochemical purity nearly 96 %. Its biodistribution data showed the high uptake and durability in the skeletal tissues without significant uptake in other major organs.The results showed that [177Lu]Lu-IBA has considerably good properties as a bone-seeking radiopharmaceutical and therefore can be a candidate for bone pain palliative therapy in skeletal metastases; however, further biological studies are still needed.
Keywords: 177Lu-IBA; bone metastases; internal dosimetry; RADAR; OLINDA/EXM; nitrogen containing bisphosphonates